Connecting to Thrive : Challenges and Opportunities of Transport Integration in Eastern South Asia - Herrera Dappe, Matias; Kunaka, Charles (Washington, DC: World Bank, 2020)
Because trucks in Bangladesh and India are not allowed to operate across the border, cargo is transloaded at the border, and Indian trucks traveling between northeast India and the rest of India must go around Bangladesh through the Siliguri Corridor, which significantly increases transport and trade costs. This lack of integration means that it is more costly for Bangladesh and India to trade with each other than for either of them to trade with Europe. As a result, bilateral trade represents only about 10 percent of Bangladesh’s trade and a mere 1 percent of India’s trade. This book presents a collection of innovative technical analyses that show what is needed to achieve seamless connectivity in the region. The report explores the extent to which the Bangladesh-Bhutan-India-Nepal Motor Vehicle Agreement (MVA) supports the cross-border operation of road transport services and identifies the gaps in the agreement that need to be addressed to improve its effectiveness. It assesses the potential shift of freight traffic to new routes and modes in eastern India and Bangladesh once the MVA is implemented and the potential impact of the MVA on wages, employment, and income in Bangladesh and India. It explores how the local impacts of a regional corridor could be enhanced in rural areas by improving access to markets along the corridors and how women’s participation in export-oriented agriculture value chains could be improved to allow women to take advantage of improved regional connectivity. "Connecting to Thrive" will be of interest to policy makers, private sector practitioners, and academics with an interest in regional connectivity in eastern South Asia.